Evolution of the Ultraviolet Upturn at 0.3 < z < 1: Exploring Helium-rich Stellar Populations - Ali Sadman S.; De Propris Roberto; Chung Chul; Phillipps Steven; Bremer Malcolm N. (IOP Publishing Ltd, 2022)
We measure the near-UV (rest-frame similar to 2400 angstrom) to optical color for early-type galaxies in 12 clusters at 0.3 < z < 1.0. We show that this is a suitable proxy for the more common far-ultraviolet bandpass used to measure the ultraviolet upturn and find that the upturn is detected to z = 0.6 in these data, in agreement with previous work. We find evidence that the strength of the upturn starts to wane beyond this redshift and largely disappears at z = 1. Our data are most consistent with models where early-type galaxies contain minority stellar populations with non-cosmological helium abundances, up to around 46%, formed at z >= 3, resembling globular clusters with multiple stellar populations in our Galaxy. This suggests that elliptical galaxies and globular clusters share similar chemical evolution and star formation histories. The vast majority of the stellar mass in these galaxies also must have been in place at z > 3.